DNA Polymerase III, but Not Polymerase IV, Must Be Bound to a τ-Containing DnaX Complex to Enable Exchange into Replication Forks - Yuan, Quan (J Biol Chem, 2016)
Examples of dynamic polymerase exchange have been previously characterized in model systems provided by coliphages T4 and T7. Using a dominant negative D403E polymerase (Pol) III α that can form initiation complexes and sequester primer termini but not elongate, we investigated the possibility of exchange at the Escherichia coli replication fork on a rolling circle template. Unlike other systems, addition of polymerase alone did not lead to exchange. Only when D403E Pol III was bound to a τ-containing DnaX complex did exchange occur. In contrast, addition of Pol IV led to rapid exchange in the absence of bound DnaX complex. Examination of Pol III* with varying composition of τ or the alternative shorter dnaX translation product γ showed that τ-, τ(2)-, or τ(3)-DnaX complexes supported equivalent levels of synthesis, identical Okazaki fragment size, and gaps between fragments, possessed the ability to challenge pre-established replication forks, and displayed equivalent susceptibility to challenge by exogenous D403E Pol III*. These findings reveal that redundant interactions at the replication fork must stabilize complexes containing only one τ. Previously, it was thought that at least two τs in the trimeric DnaX complex were required to couple the leading and lagging strand polymerases at the replication fork. Possible mechanisms of exchange are discussed.